Perancangan Interior Museum Musik Klasik Berbasis Media Berteknologi Tinggi untuk Anak-anak di Surabaya - Fenny Kurnia D, Sugianto Wijaya Hedy C. Indrani (Intra, 2013)
Classical Music in Indonesia is one of the art sound that can affect human feelings. With music we can feel the serenity, spirit, and emotions separately in each genre. It is important for us to preserve classical music as art and culture, which can evoke appreciation of country music product. In addition to reviving public facility that is currently experiencing a setback therefore we need a facility that can inform openly a collection that is, through a Classical Music Museum in Surabaya which can provide education and fun entertainment. By creating an atmosphere that industrial look of pure material, with the use of the applicative and innovative media.